1999
DOI: 10.1136/gut.45.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal crypt cell apoptosis in murine acute graft versus host disease is mediated by tumour necrosis factor α and not by the FasL-Fas interaction: effect of pentoxifylline on the development of mucosal atrophy

Abstract: Background-Murine T cell mediated acute semiallogeneic graft versus host disease (GVHD) is characterised by lymphocytic infiltrates, crypt hyperplasia, and villous atrophy. It has been shown that programmed cell death (apoptosis) of the crypt epithelium takes place during the intestinal manifestation of acute GVHD. Aims-To investigate which of the two most investigated inductors of apoptosis (Fas ligand (FasL) and tumour necrosis factor (TNF-)) is responsible for the induction of apoptosis in this animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
(32 reference statements)
3
31
0
Order By: Relevance
“…In certain inflammatory conditions, such as celiac disease, nematode infections, and graft-versus-host disease, the numbers of apoptotic nuclei were increased in villus epithelial cells (32)(33)(34)(35). In addition, the involvement of dysregulation of the apoptotic process in intestinal epithelial cells in inflammatory bowel diseases and colon cancer has also been suggested (36,37).…”
Section: Discussionmentioning
confidence: 95%
“…In certain inflammatory conditions, such as celiac disease, nematode infections, and graft-versus-host disease, the numbers of apoptotic nuclei were increased in villus epithelial cells (32)(33)(34)(35). In addition, the involvement of dysregulation of the apoptotic process in intestinal epithelial cells in inflammatory bowel diseases and colon cancer has also been suggested (36,37).…”
Section: Discussionmentioning
confidence: 95%
“…Early injury to the gut epithelium allows for the transmission of LPS into the systemic circulation and peripheral tissues, with subsequent activation of macrophages, and release of high levels IL-1 and TNF-α (31,32). Both of these inflammatory cytokines have established roles in the pathogenesis of lethal GVHD (26,30,(33)(34)(35)(36)(37). The finding that MHC class II expression by host nonhematopoietic target tissues in the [B6→B6.MHC II -/-] chimera was not essential for the cascade of inflammatory events that ultimately lead to GVHD and lethality (9) suggested that, in such models, either large amounts of systemic cytokines alone are sufficient to cause severe tissue injury, or resident allogeneic B6 APCs in the tissues are adequate to activate infiltrating T cells to mediate injury via localized cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TNF-␣ as a major effector molecule of GVHD has been confirmed in several experimental systems. Importantly, neutralizing anti-TNF-␣ antibodies have been shown to alleviate cutaneous and intestinal GVHD in both mice and humans (Piguet et al, 1987;Herve et al, 1992;Brown et al, 1999;Stuber et al, 1999). Blockade of the CD40-CD154 co-stimulatory pathway of antigen presentation prevented GVHD following allogeneic BMT (Durie et al, 1994;Blazar et al, 1998;Seung et al, 2000).…”
Section: Graft-vs-host Disease and Olpmentioning
confidence: 99%